Key Components of the Financial Infrastructure of the Digital Economy Within the Fuel and Energy Complex - Aleksandrovna Zavalko, Natalia; Evgenievna Matyunina, Olga; Anatolyevna Izmaylova, Svetlana; Olegovna Kozhina, Veronika; Anatolevich Lebedev, Konstantin (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to provide an outline of key components of the financial infrastructure of the digital economy within the fuel and energy complex. It is established that the formation of global financial architecture, including in the context of development of elements of the digital economy within the fuel and energy complex, is currently accompanied by a sharp acceleration in global cash flows and considerable growth in the international market for electronic money and electronic currencies. The authors prove that, owing to the informatization of the fuel and energy sector and the emergence of new financial technologies, many investors today will find it easier to access international markets. It is also suggested that currently there is a positive trend in the pace of growth in digital services for financial infrastructure, which are attracting significant volumes of investment, with the trend projected to intensify in the near future. In the authorsâ€™ view, the key factors that will govern the effectiveness of components of the financial infrastructure of the digital economy within the fuel and energy complex are innovations, transparency, and accessibility.Â Â